Validity of Multimedia Peat Swamp Forest Concept Based on Problem Solving to Practice Critical Thinking Skills of Chemistry Students - Betty Agustina; Danang Biyatmoko; Aminuddin Prahatama Putra (Master Program of Biology Education, Universitas Lambung Mangkurat, 2020)
The wetland learning system is still conventional and lecturer-centered so that students are not accustomed to doing problem solving activities that have an impact on the lack of students' critical thinking skills. This study aims to develop multimedia learning of problem solving based peat swamp forest concepts to determine the validity of multimedia to train students' critical thinking skills. The stages carried out following the ADDIE instructional design flow include analysis, design, development, implementation and evaluation. Data collection techniques used a validation sheet instrument for two material experts from Lambung Mangkurat University and one multimedia expert from Politeknik Hasnur. Readability test was conducted on three active students who had taken a course to introduce the wetland environment in FMIPA ULM. The results showed that the multimedia learning concept of problem solving peat swamp forest to train critical thinking skills of chemistry students of FMIPA ULM Banjarbaru is very valid.AbstrakSistem pembelajaran lahan basah masih bersifat konvensional dan berpusat pada dosen sehingga mahasiswa tidak terbiasa melakukan kegiatan pemecahan masalah yang berdampak pada kurangnya keterampilan berpikir kritis mahasiswa. Penelitian ini bertujuan untuk mengembangkan multimedia pembelajaran konsep hutan rawa gambut berbasis problem solving untuk mengetahui bagaimana validitas multimedia untuk melatihkan keterampilan berpikir kritis mahasiswa. Tahapan yang dilakukan mengikuti alur desain instruksional ADDIE meliputi analisis, desain, pengembangan, implementasi dan evaluasi. Teknik pengumpulan data menggunakan instrumen lembar validasi terhadap dua ahli materi dari Universitas Lambung Mangkurat dan satu ahli multimedia dari Politeknik Hasnur. Uji keterbacaan dilakukan terhadap tiga mahasiswa aktif yang pernah mengambil mata kuliah pengenalan lingkungan lahan basah di FMIPA ULM. Hasil penelitian menunjukkan bahwa multimedia pembelajaran konsep hutan rawa gambut berbasis problem solving untuk melatihkan keterampilan berpikir kritis mahasiswa kimia FMIPA ULM Banjarbaru sangat valid.